The Essence And Curriculum Of Learning Indonesian Language In Elementary Schools - Ery Maritim (Pusat Riset dan Inovasi Nasional, 2023)
Education in elementary schools is the initial momentum for students to improve all the abilities inherent in children. Starting at the time of learning in early childhood (kindergarten ) and then continued and strengthened in elementary school. Habits that children carry out every day, both in the home, community and school environment, are important in forming natural potential, especially in the field of children's language. Language skills that are expected to be assisted, grown, and used as development material for elementary school teachers include listening or listening skills, speaking, reading, and writing. These four skills are so important to be given at the elementary school level as a form of teaching Indonesian according to the current education curriculum. Learning activities in schools are also expected to be able to integrate this unified language in all intra- and extra-curricular activity programs so that their benefits are increasingly visible and meaningful in harmony with the social life of students.